Acute Impacts of Different Types of Exercise on Circulating α-Klotho Protein Levels - Iturriaga, Tamara; Yvert, Thomas; Sanchez-Lorente, Isabel M.; Diez-Vega, Ignacio; Fernandez-Elias, Valentin E.; Sanchez-Barroso, Lara; Dominguez-Balmaseda, Diego; Larrosa, Mar; Perez-Ruiz, Margarita; Santiago, Catalina (Frontiers in Physiology, 2021)
INTRODUCTION: Elevated plasma α-klotho (αKl) protects against several ageing phenotypes and has been proposed as a biomarker of a good prognosis for different diseases. The beneficial health effects of elevated plasma levels of soluble αKl (SαKl) have been likened to the positive effects of exercise on ageing and chronic disease progression. It has also been established that molecular responses and adaptations differ according to exercise dose. The aim of this study was to compare the acute SαKl response to different exercise interventions, cardiorespiratory and strength exercise, in healthy physically active men and to examine the behaviour of SαKl 72 h after acute strength exercise. METHODS: In this quasi-experimental study, plasma SαKl was measured before and after a cardiorespiratory exercise session (CR) in 43 men, and a strength exercise session (ST) in 39 men. The behaviour of SαKl was also examined 24, 48 and 72 h after ST. RESULTS: Significant differences (time x group) were detected in SαKl levels (p=0.001; d=0.86) between CR and ST. After the ST intervention, SαKl behaviour varied significantly (p=0.009; d=0.663) in that levels dropped between pre- and post exercise (p=0.025; d=0.756) and were also significantly higher compared to pre ST values at 24 h (p=0.033; d=0.717) and at 48 h (p=0.015; d=0.827). CONCLUSIONS: SαKl levels increased in response to a single bout of cardiorespiratory exercise and while they decreased immediately after strength exercise, levels were elevated after 24 h indicating different klotho protein responses to different forms of exercise.